Individualisation and growing diversity of employment relationships - Brown, William; Marsden, David (London, 2010)
"At a time when the economic recession is more severe, and trade unions are weaker, than at any time since the War, it would be unproductive to speculate about the extent to which these changes have been imposed, acquiesced, or agreed by the workers concerned. Instead we focus on recent changes in employment relationships in Britain, and their consequences, and then on the winners and losers, which provides a cue for considering the longer term desirability of some of these developments for social justice and cohesion."